A song for the brokenhearted - Shaw, William, 1959- (A Breen and Tozer mystery, 2016)
The earthshaking year of 1968 comes to a sweeping and dangerous close as Detectives Breen and Tozer battle the most powerful members of London society in their probe into a case going back years--the murder of Tozer's younger sister.